Investigation of soil water hydrological process in the permafrost active layer using stable isotopes. Issue 12 (21st April 2020) - Li, Zongjie; Ma, Jinzhu; Song, Lingling; Gui, Juan; Xue, Jian; Zhang, Baijuan; Gao, Wende; Li, Zongxing
Abstract: Here, we studied the isotope characteristics and source contributions of soil water in the permafrost active layer by collecting soil samples in July 2018 in Yangtze River basin. Soil moisture and temperature showed decreasing trends from 0–80 cm, and an increasing trend from 80–100 cm. The value of δ 18 O and δD first increased and then decreased in the soil profile of 0–100 cm; however, d‐excess increased from 0–100 cm. δ 18 O values became gradually positive from the southwest to northeast of the study area, while d‐excess gradually increased from southeast to northwest. The evaporation water line (EL) was δD = 7.56 δ 18 O + 1.50 (R 2 = 0.90, p < 0.01, n = 96). Due to intense solar radiation and evaporation on the Tibetan Plateau, the elevation did not impact the surface soil. The altitude effect of the soil depths of 0–20 cm was not obvious, but the other soil layers had a significant altitude effect. Soil moisture and temperature were closely related to the stable isotopic composition of soil water. The contribution of precipitation to soil water on the sunny slope was 86%, while the contribution of the shady slope was 84%. However, the contribution of ground ice to soil water on sunny slope was 14% and the shady slope was 16%. The contribution of ground ice to soil water increased with increasing altitude on the sunny slope, but the contribution of ground ice to soil water had no obvious trend on the shady slope. Abstract : Soil water mainly comes from precipitation and ground ice in alpine region. The contribution of precipitation to soil water in the sunny slope was 86%, while the contribution of shade slope was 84%. The contribution of ground ice to soil water showed an increasing trend with the increasing of altitude in sunny slope.